The role of transformation of marketing functions to ensure innovative development of retail enterprises - Proskurnina, Nadiia (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2020)
The subject of research is the study of the transformation of classical marketing functions (analytical, production, sales and management and control) under the influence of market development factors and the transformation of marketing in the context of structural changes in the economy. Marketing functions are a set of certain activities carried out by retail operators as a market participant. The aim is to determine the role of the transformation of marketing functions to ensure the innovative development of enterprises. The objective is to study the gradual development of marketing and exchange processes that occurred with its functions under the influence of transformational phenomena in the economy. After all, the development of online commerce required new approaches to understanding the classic features and it became extremely important to interest the consumer and force him to place an order in a particular online store. General scientific methods are used: analytical method, which helps to highlight the stages of development of approaches to the essence of marketing in the object of historical research; induction method - to generalize the approaches and directions of marketing transformation. The following results of the study was the conclusion that the development of marketing systems not within the manufacturers themselves, but within retail operators in order to sell products to end users becomes the basis of the management and control function. It is revealed that in modern conditions the functions of control over production for the purpose of sale began to be performed by the marketing departments of retail operators, began to study the market and issue orders for production for the purpose of sale. Thus, marketing becomes an intermediary between manufacturers and retail operators. Conclusions: on the basis of the transformed marketing functions the business processes in the field of marketing which are carried out by the retail operator are allocated. It has been proven that an effective marketing investment plan must take into account all activities that can help the retail operator to influence consumer demand and realize the potential for profitable growth. The retailer should develop simple, flexible optimization tools using qualitative and quantitative indicators to evaluate.